The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1540-6520.2009.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Arrangements and International Entrepreneurship: The State as Institutional Entrepreneur

Abstract: We examine the role of the state as entrepreneur and institutional entrepreneur in the Middle East. Using historical event sequencing methodology we seek to understand the rise of Dubai and the United Arab Emirates as a context for international entrepreneurship. We build on ideas at the intersection of international entrepreneurship and institutional theory to develop a set of propositions that enhance our understanding of international entrepreneurship. We provide implications for the management of both glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 107 publications
3
51
2
2
Order By: Relevance
“…Nasra and Dacin (2010) trace the evolution of Dubai state rulers as institutional entrepreneurs who have created more IE opportunities there than elsewhere in the region. Dechant and Lamky (2005) find that the obstacles faced by female entrepreneurs in Bahrain and Oman are generally similar to those faced by their counterparts in other parts of the world, although the underlying reasons for these obstacles are somewhat unique, reflecting the Arab and Islamic values that infuse these cultures.…”
Section: Middle East and North Africamentioning
confidence: 99%
“…Nasra and Dacin (2010) trace the evolution of Dubai state rulers as institutional entrepreneurs who have created more IE opportunities there than elsewhere in the region. Dechant and Lamky (2005) find that the obstacles faced by female entrepreneurs in Bahrain and Oman are generally similar to those faced by their counterparts in other parts of the world, although the underlying reasons for these obstacles are somewhat unique, reflecting the Arab and Islamic values that infuse these cultures.…”
Section: Middle East and North Africamentioning
confidence: 99%
“…Child and his colleagues (Child et al, 2007) examined institutional entrepreneurship in the development of China's environmental protection systems over 30 years and outlined the various roles of institutional entrepreneurs, presuming in this context that dominant roles were played by the government. A recent study suggests that international entrepreneurship in Dubai was the outcome of the government's active involvement as the agent of change (Nasra and Dacin, 2010). However, the relationship between state and entrepreneur continues to be unclear, although the Chinese government is attempting to embrace the private sector (Luo and Junkunc, 2008).…”
Section: Formal Institutions and The Role Of Governmentmentioning
confidence: 98%
“…By putting institutional structures in place, governments and states can encourage and foster industry creation as well as entrepreneurship (Spencer et al, 2005). A recent study found that international entrepreneurship in Dubai was the outcome of the government's active involvement as the change agent (Nasra and Dacin, 2010). From the political economy viewpoint, institutional escapism and governmental promotion are logically complementary with each other to offset the disadvantages of emerging market enterprises in global competition (Luo et al, 2010).…”
Section: Institutional Voidsmentioning
confidence: 99%